2006
DOI: 10.1177/106591290605900412
|View full text |Cite
|
Sign up to set email alerts
|

Who’s Whispering in Your Ear? The Influence of Third Parties Over State Agency Decisions

Abstract: S tate administrative agencies play a critical role in the policymaking process in the United States. However, within both policy formation and implementation, state agencies do not act alone. Rather, agencies are challenged to balance the preferences of a number of powerful constituencies-in particular, governors, legislators, and interest groups. Despite the importance of both agencies and third parties to the policy process in the American states, there have been few theoretical and empirical studies dedica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…As the grant progressed, grantees spoke increasingly of the importance of in-person meetings and establishing ongoing working relationships with decision-makers, such as participation on committees and work groups that include a representative from the county board of supervisors and regular presentations to decision-makers on the clinic role in addressing the health care needs of the uninsured. The grantee perceptions of the importance of the quality and frequency of their interactions with decision-makers are supported by the findings by Kelleher and Yackee (2006) Considered a difficult-to-measure, "messy" area of inquiry, the evaluation of advocacy groups, their activities, and the outcomes of their campaigns pose many challenges (Coates & Rosalind, 2002). First, it is difficult to attribute a specific advocacy activity to a particular policy outcome, and less obvious activities may be more important in determining a policy outcome.…”
Section: Gaining Access To and Establishing Partnerships With Decisiomentioning
confidence: 69%
See 1 more Smart Citation
“…As the grant progressed, grantees spoke increasingly of the importance of in-person meetings and establishing ongoing working relationships with decision-makers, such as participation on committees and work groups that include a representative from the county board of supervisors and regular presentations to decision-makers on the clinic role in addressing the health care needs of the uninsured. The grantee perceptions of the importance of the quality and frequency of their interactions with decision-makers are supported by the findings by Kelleher and Yackee (2006) Considered a difficult-to-measure, "messy" area of inquiry, the evaluation of advocacy groups, their activities, and the outcomes of their campaigns pose many challenges (Coates & Rosalind, 2002). First, it is difficult to attribute a specific advocacy activity to a particular policy outcome, and less obvious activities may be more important in determining a policy outcome.…”
Section: Gaining Access To and Establishing Partnerships With Decisiomentioning
confidence: 69%
“…Additionally, some advocacy tactics may be more influential than others. For example, Kelleher and Yackee (2006) found that interest groups that spent time with bureaucrats were more likely to influence state-agency rulemaking than those that did not. Collecting, analyzing, and disseminating information on key policy issues may be more important than other advocacy activities to secure access to It is exceedingly difficult to assess the actual influence of these groups on policymaking, such as decisionmaker support for a specific policy.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, structural insulation may be more or less permeable. Politicians, at various jurisdictional levels have a wide range of indirect institutional mechanisms and informal influence mechanisms that can permeate, circumvent, or simply overpower formal ownership isolating mechanisms (Thatcher 2002;Kelleher and Webb Yackee 2006). Baranowski (2007, 1220) describe some of the more indirect methods that state governors in the U.S. increasingly utilize to strengthen their influence over state bureaucracies, including, for example, the use of economic analysis mandates (Cooper and West 1988;Hahn 2000).…”
Section: Public Agency External Analysis 81mentioning
confidence: 98%
“…Yackee and Yackee (2006) analyzed the business bias in the incorporation of nearly 1700 comments regarding 30 regulations by four government regulatory agencies. Kelleher and Yackee (2006) observed informal contacts -phone calls and personal meetings -conducted by legislators, governors and interest groups in an attempt to influence regulatory agencies. To do so, they relied on surveys conducted with decision-makers from about 80 regulatory agencies in the 50 U.S. states.…”
Section: Interest Groups and Bureaucracymentioning
confidence: 99%